ХАЛЫҚ ҚОСЫҚЛАРЫНДА ИМПРОВИЗАЦИЯ ДƏСТҮРИ - Матимов, К.Г. (FAN va JAMIYAT, 2021)
The article examines the historical processes, genres and features of the formation of Karakalpak folk songs, the origins of the tradition of improvisation in folk songs, the stages of formation, the history of development.